The Effect of Early Mobilization Implementation on the Healing of Sectio Caesarea Operation Wounds at Harapan Insan Sendawar Hospital - Verenia; Jasmawati; Rifan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2022)
Sectio caesarea has become a safe procedure with consideration for the safety of the mother and baby. Early postoperative mobilization has been advocated for patients undergoing major surgery to increase functional capacity and to improve recovery. The purpose of this study was to determine the effect of early mobilization on surgical wound healing at Harapan Insan Sendawar Hospital. This type of research is Quasy Experiment with a static grub comparison research design. A sample of 32 postpartum post-partum mothers with sectio secarea with 16 respondents in the intervention and control groups respectively. The sampling method is non-probability sampling with purposive sampling technique. There is an effect of early mobilization with SC wound healing at Harapan Insan Sendawar Hospital (p-value 0.036).